Evaluation of the genetic diversity and population structure of potential Bosnian mountain horse based on microsatellite markers (VETERINARIA, 2021)
The focus of this study was to evaluate the genetic diversity and population structure of potential Bosnian mountain horse and todetermine the possible sources of undoubtedly autochthonous germplasm using microsatellite markers. Genomic DNA was extracted from the whole blood collected from 61 potential Bosnian mountain horse specimens divided into three groups according to the population of origin and genotyped by using 17 specific microsatellite markers. Existence of higher genetic variability was obtained in Group 1 and 3. Group 2 showed genetic specificity as well as high level of heterogeneity. An increased inbreeding coefficient was detected in Group 1 and 3 (0.1678 and 0.1813, respectively). Deviation from HardyWeinberg equilibrium was noticed in Group 1 and 3. Analysis of molecular variance showed that from all genetic variation, 5% was among populations, 14% among individuals and 81% within individuals. Results of the fixation index showed moderate level of genetic differentiation among groups (5.1%). The results of pairwise differences showed clear genetic differentiation among Group 2 and other observed groups. Analyses of admixture model showed that second cluster consist almost all individuals from Group 2, since other clusters consists individuals from two other observed groups. Factorial Component Analysis has confirmed results of admixture model. Group 2 has indications the most genetically characteristics of autochthonous Bosnian mountain horses. Results of genetic diversity and F statistic data indicate that in the gene pool of Group 1 and 3 is present a part of the gene pool of other breeds.
Keywords: autochthonous breed; genetic diversity; gene pole; genetic structure; microsatellites